Latina Province, Italy - Robert G. Harland (2016)
This panoramic view of the Latina Province (formerly Littoria Province) in Italy shows, to some extent, the canal and road infrastructure and the city of Latina in the distance. Photographed in July 2016 from Via Norbana on the road to Norma, looking west, the well irrigated, fertile landscape benefits from the extensive network of canals built during the fascist period of rule. This undertaking of large infrastructure projects at the regional level happened as part of the region's reclamation of what had previously been a mosquito and malaria infested marshland.